2023
DOI: 10.1039/d2su00089j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanocatalytic hydrogenolysis of benzyl phenyl ether over supported nickel catalysts

Abstract: Mechanocatalysis is a promising approach for green, solvent-free biomass deconstruction and valorization. Here, the hydrogenolysis of benzyl phenyl ether (BPE), a model lignin ether, via ball milling is demonstrated over...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 77 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…The final alkane products form through the combination of produced alkyl radicals and atomic hydrogens over metallic surfaces which usually accounts for H 2 dissociation in thermal catalytic hydrogenation reactions 42 , 43 . H 2 dissociation by mechanocatalysis should be feasible, on account of the reported work of ammonia synthesis 21 23 and hydrogenolysis of benzyl phenyl ether 44 under ambient hydrogen pressure, where H 2 dissociation is indispensable. Moreover, hydrogen dissociation also occurs on the metals used even without mechanical forces.…”
Section: Resultsmentioning
confidence: 99%
“…The final alkane products form through the combination of produced alkyl radicals and atomic hydrogens over metallic surfaces which usually accounts for H 2 dissociation in thermal catalytic hydrogenation reactions 42 , 43 . H 2 dissociation by mechanocatalysis should be feasible, on account of the reported work of ammonia synthesis 21 23 and hydrogenolysis of benzyl phenyl ether 44 under ambient hydrogen pressure, where H 2 dissociation is indispensable. Moreover, hydrogen dissociation also occurs on the metals used even without mechanical forces.…”
Section: Resultsmentioning
confidence: 99%
“…[1] About one-third of global CO 2 emissions come from industrial processes (≈26%) and heavy-duty transportation (≈8%), [1][2][3] which are particularly difficult to decarbonize. Green hydrogen can play a unique role in achieving net zero for these sectors, [4] either as storage/carrier of renewable energy (e.g., fuel for freight transportation or industrial process heat), [5][6][7][8] as a replacement to fossil hydrogen (e.g., in petro/bio-refining or ammonia production), [9][10][11][12][13] or as an alternative chemical reagent (e.g., metal refining). [14] For this reason, the International Energy Agency has projected that the global usage of hydrogen will increase from 90 to 500 Mtpa (million tonnes per annum) to reach net zero by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of mechanocatalysis as an approach to depolymerizing lignocellulosic biomass and lignin model compounds have been conducted. ,, Rinaldi et al demonstrated the depolymerization of both cellulose and biomass to water-soluble sugars and furfurals with complete conversion and yields of water-soluble oligosaccharides and lignin oligomers exceeding 90%. Bolm’s works have examined the conversion of lignin model compounds representing β-O-4 linkages in base-catalyzed and oxidative reactions . The base-catalyzed reactions produced monomer yields of up to 94%, while the oxidative transformation resulted in aryl-c α cleavage of the β-O-4 model, resulting in quinone (91% yield) and guaiacol (82% yield) as the two main products.…”
mentioning
confidence: 99%
“…The base-catalyzed reactions produced monomer yields of up to 94%, while the oxidative transformation resulted in aryl-c α cleavage of the β-O-4 model, resulting in quinone (91% yield) and guaiacol (82% yield) as the two main products. Sievers et al recently demonstrated hydrogenolysis of the α-O-4 bond in the lignin model compound, benzyl phenyl ether (BPE), over supported Ni catalysts . Due to the similar bond strengths, this ether bond can be considered representative of the β-O-4 linkages found in lignin.…”
mentioning
confidence: 99%